(NiNTEGRALXNYE URAWNENIQ (B:s (Nu^EBNOE POSOBIE (B/s - (NwASILXEWA(B, (NaDELAIDA bORISOWNAs; (NtIHONOW(B, (NnIKOLAJ aNDREEWI^s ((NmOSKWA (B:s (NiZD(B-(NWO mgu(B,s, 1989)
(NpREDM(B. (NUKAZ(B.: (NS(B. 157s
(NbIBLIOGR(B. 31 (NNAZW(B.s
Keywords: (NiNTEGRALXNYE URAWNENIQs